Terminal Sliding Mode Control for Dynamic Voltage Restorer - Inamdar, Jeevan J.; Annapoorani, K. Iyswarya (Distributed Generation & Alternative Energy Journal, 2022)
Day by day the increment in non-linear load has deteriorated the Voltage Quality of power supply system. The crucial concerns originated are Voltage Sag and Voltage Harmonics. These power quality problems cause a lot of losses in the power system which results in commercial losses as well. The moderation of these issues within the permissible limits is much needed. Among, the several methods and devices that exist, the Dynamic Voltage Restorers (DVR) are often used. This paper focuses on mitigation of Volt- age Sag and Voltage Harmonics. In the development phase of DVR, the design of controller is an important phase to be considered. The nonlinear control approach of design is superior to linear control. In this paper the Terminal Sliding Mode Control is used for designing the controller for DVR. To improve accuracy and robustness, an additional nonlinear quantity has been introduced to the equation of traditional Sliding Mode control. The Dynamic Voltage Restorer is modelled using MATLAB/Simulink and used for studies. The simulation results presented validates effectiveness of the proposed control approach.